Keadilan dan Kebebasan bagi Masyarakat Plural di Indonesia: Refleksi Pemikiran Islam Nurcholish Madjid - Pattimahu, Muhammad Asrul; Jamaa, La; Pariela, Tonny D; Toisuta, Hasbollah (Program Pascasarjana UKIM, 2024)
In Indonesia's pluralistic society, implementing the values of justice and freedom often faces significant challenges. Differences in religion, culture, and socio-economic backgrounds necessitate a nuanced understanding of interpreting and applying justice that is not confined to any single group. This article presents an in-depth exploration of Islamic perspectives on the concepts of justice and freedom, focusing primarily on the thoughts of Nurcholish Madjid (Cak Nur) as the main subject of study. This research is a literature review of Cak Nur’s works and scholarly studies of his ideas using a qualitative descriptive method for data analysis. The study finds that while justice, as articulated by Cak Nur, is a cosmic law applicable to all communities and social classes, its implementation must consider the social realities of a diverse society. Similarly, the concept of freedom, viewed as a prerequisite for creating an inclusive and egalitarian society, requires careful attention to the levels of maturity and social development within a pluralistic context.